Desire for Fetal Sex Selection among Pregnant Women Attending Antenatal Clinic - Khanal, Archana (Patan Prospective Journal, 2022)
Viewing the situation of fetal sex selection, this study aims to identify the knowledge of fetal sex selection among pregnant women and to analyze the practice of fetal sex selection among pregnant women attending antenatal clinic. The general objective of the study is to assess the desire for fetal sex selection among pregnant women. This study was conducted at Patan Hospital, Lalitpur. The research was carried out using tools such as the interview-checklist. Study findings reveal that fetal sex selection is indicated in genetic disorders of the fetus but not indicated for non-medical reasons. Fetal sex selection has both positive and negative impacts on society. However, female feticide should be prohibited on the basis of fetal sex selection practice.